A COMPARISON OF ESSENTIAL OIL EXTRACTION FROM THE LEAVES OF LEMONGRASS (CYMBOPOGON NARDUS L.) USING TWO MICROWAVE-ASSISTED METHODS - Mahfud, Mahfud; Ma'sum, Zuhdi; Bhuana, Donny Satria; Altway, Ali; Yuniati, Yuyun (Journal of Applied Engineering Science, 2022)
The extraction of essential oils from Lemongrass leaves (Cymbopogon nardus L.) has become more promising than ever before due to the oils' increasing demand in the market in addition to the dynamic breakthrough in its technology advancement. This study presents a comparison of two different methods of microwave-assisted essential oil extraction, namely Microwave Hydrodistillation (MHD) and Solvent-Free Microwave Extraction (SFME), both of which exhibit a better quality in terms of essential oil recovery compared to the conventional extraction methods. This study investigated the effect of extraction time, microwave power, as well as  feed-to-distiller volume ratio (F/D). Experimental results suggest that although there is a tendency to increase yield along with the increasing power, the yield turns out to decrease at higher power, with the optimum power for the MHD method being 420 W and that of the SFME method being 560 W. Smaller F/D ratios appear to give higher yields for both methods and the smaller the size of the material, the higher the yield obtained. The MHD method produces a smaller yield but has a better quality of citronella oil compared to the SFME method. Two first-order and second-order extraction kinetics models were compared for both the MHD and SFME methods, and the results suggest that the first-order model was slightly better at representing the experimental data based on the RMSD and R2 values. This applies to both experimental data using the MHD and SFME methods, respectively.
Keywords: extraction, lemongrass oil, microwave hydrodistillation (MHD), solvent free microwave extraction (SFME)